ANALYSIS OF E-CRM APPLICATION IN PROMOTING MARKETING OF ALUMINUM WARDROBE IN GONDRONG SERVICE STORE - Fany Azura; Adi Prijuna Lubis; Maulana Dwi Sena (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Background: In an era of increasingly advanced technology, stability of the world economy, and the ever-advancing globalization of trading systems, the sales conditions of companies are becoming narrower and narrower. With the increase of domestic and foreign competitors, the company's domestic and international performance is expected to be able to compete in the market. Method: This research method is conducted with the purpose of explaining the actual situation and uses a qualitative method that is related to the problem under investigation. Result: The results of this study can design customer relationship management (CRM) as a strategy to achieve customer satisfaction, increase loyalty, and find new customers. With CRM, customers can make purchases more easily, Gondrong Service Store manages sales data more easily. Conclusion: Gondrong Service Store's E-CRM application, using this PHP programming language, can manage sales of aluminum cabinets online, so that customers can directly interact in sales transactions. This E-CRM application is designed to facilitate more effective promotion of products and develop sales of products to customers, especially customers outside of Batu Bara area. So that they can manage sales and attract more customers outside of Batu Bara area by ordering online.